Analisis Dampak Ikhtikar Bahan Pangan terhadap Perekonomian Indonesia Pemikiran Yusuf Al-Qardhawi - Ida Hapni Harahap; Sri Sudiarti; Tuti Anggraini (ITB AAS INDONESIA, 2023)
The need for staple goods is a need to ensure survival. Staple goods are goods that concern the livelihoods of many people with a high scale of meeting needs and are a supporting factor for people's welfare. The practice of hoarding has always received serious scrutiny from various parties, especially the government, to eradicate it so that the prices of various basic necessities in the market return to normal. The skyrocketing food prices are not the first time. However, it seems that the government is not ready to anticipate this phenomenon. So this keeps happening over and over again. The causes of skyrocketing prices include, among others, due to a lack of food stocks, drought, pest attacks, uneven distribution, to the hoarding of goods. Hoarding of goods is buying something in large quantities, so that the goods are reduced in the market so that the price (of the goods being hoarded) will increase and when the price increases then they will be released (sold) to the market, thus getting multiple profits. According to Yusuf Al-Qardhawi hoarding is forbidden if it has the criteria of being carried out in a place where the population will suffer because of the hoarding. Hoarding is done to increase prices so that people find it difficult and so that they can get multiple benefits. This research is a library research (library research. The conclusions that can be drawn in this study, one of the items that are often stockpiled by traders to gain large profits are staples. If an overview of staples occurs, it will unsettle the community, especially the middle class, to meet their daily needs. Day According to Yusuf Al-Qardhawi the prohibition of hoarding goods is that the practice of ihtikar can cause socio-economic disturbances. This harm arises from storing an item. By hoarding and then increasing prices so that people's purchasing power will decrease even though people really need these goods it will very pleased